The potential of youth workers as facilitators of values formation and development. - Krauss, Steven Eric; Suandi , Turiman (2008)
Youth workers everywhere are engaged in a daily revolution to facilitate change within young people, often with limited resources, support and infrastructure. They do this work through the developmental relationships that they form with their young clients. However, to achieve their goals and reap the rewards of their efforts, youth workers must be effective agents of change. The focus of this article is to further understand the notion of youth workers as change agents, in the context of developing values among the young people with whom they work. The role of values in youth work, the formation and development of values in youth, transformative learning approaches, the steps in experiential learning and youth-work pedagogies that use models of how youth learn are also discussed. With the increasing demands on youth workers to facilitate change in the lives of their young clients, these groups need professional training and education to prepare them to do the critical work of youth development.